Low Tidal Volume Positive End-Expiratory Pressure versus High Tidal Volume Zero-Positive End-Expiratory Pressure and Postoperative Pulmonary Functions in Robot-Assisted Laparoscopic Radical Prostatectomy - BİLGİLİ, BELİZ; UMUROĞLU, TÜMAY (KARGER, 2017)
Objective: The aim was to compare the effects of low tidal volume (V-T) and moderate positive end-expiratory pressure (PEEP) with high V-T and zero end-expiratory pressure (ZEEP) on postoperative pulmonary functions and oxygenation in patients undergoing robot-assisted laparoscopic radical prostatectomy. Subjects and Methods: Forty-four patients were randomized into low V-T-PEEP and high V-T-ZEEP groups. The patients were ventilated with a V-T of 6 mL/kg and 8 cm H2O PEEP in the low V-T-PEEP group and a V-T of 10 mL/kg and 0 cm H2O PEEP in the high V-T-ZEEP group. Preoperative and postoperative spirometric measurements were done and chest X-rays were evaluated using the radiological atelectasis score (RAS). p < 0.05 was considered statistically significant. Results: The intraoperative and postoperative arterial partial pressure of oxygen and arterial oxygen saturation values were significantly higher in the low V-T-PEEP group than in the high V-T-ZEEP group. At all times, the arterial-to-alveolar oxygenation gradients were significantly lower in the low V-T-PEEP group than in the high V-T-ZEEP group. Preoperative RAS were similar in both groups, but the postoperative RAS was significantly lower in the low V-T-PEEP group (p < 0.001). Forced vital capacity, forced expiratory volume in 1 s, and peak expiratory flow rate recorded postoperatively were significantly lower in the high V-T-ZEEP group (p < 0.001). Conclusions: Postoperative pulmonary functions were less impaired in patients ventilated with a V-T of 6 mL/kg and 8 cm H2O PEEP than in patients ventilated with a V-T of 10 mL/kg and ZEEP. (C) 2017 The Author(s) Published by S. Karger AG, Basel
Keywords: Pneumoperitoneum; Steep Trendelenburg; Low tidal volume; Positive end-expiratory pressure; Pulmonary function; Robot-assisted surgery; STEEP TRENDELENBURG POSITION; LUNG-PROTECTIVE VENTILATION; CONTROLLED-TRIAL; SURGERY; PNEUMOPERITONEUM; COMPLICATIONS; OUTCOMES; UROLOGY